Molecular epidemiology of Staphylococcus epidermidis in neonatal intensive care units. Issue 1 (16th November 2016) - Soeorg, Hiie; Huik, Kristi; Parm, Ülle; Ilmoja, Mari‐Liis; Metsvaht, Tuuli; Lutsar, Irja
Abstract : Late‐onset sepsis (LOS) in preterm neonates is increasingly reported to be associated with gut‐colonizing Staphylococcus epidermidis . We aimed to describe the molecular epidemiology of S. epidermidis colonizing the gut of neonates hospitalized in two neonatal intensive care units. S. epidermidis from rectal swabs were typed by multilocus variable‐number tandem‐repeat analysis (MLVA), randomly chosen isolates of predominant MLVA types additionally by multilocus sequence typing. Antimicrobial susceptibility, the presence of icaA, IS 256, arginine catabolic mobile element (ACME), agr type, and SCC mec type were determined. Of 276 neonates (38.4%), 106 were colonized with S. epidermidis, yielding a total of 139 isolates (62 in one unit and 77 in another unit). Of the 55 MLVA types identified, the five predominant detected in both units corresponded to sequence type (ST) 2, ST5, and ST59 or its single locus variant ST81 and formed three major MLVA clonal complexes accounting for 74.8% of all isolates. Overall, the prevalence of mecA, icaA, IS 256, and ACME was 91.4%, 28.1%, 64%, and 77%, respectively. Of the mecA ‐positive isolates (n = 127), 43.9% carried SCC mec type IV. Of eight episodes of LOS, four were caused by ST2 and two by ST5. Preventing gut colonization with nosocomial epidemic S. epidermidis in hospitalized neonates could contribute to the prevention of LOS.